IMPLEMENTASI HUKUM KELUARGA SEBAGAI REKAYASA SOSIAL MASYARAKAT DALAM UPAYA MENINGKATKAN KESADARAN HUKUM DAN KEPATUHAN HUKUM - Ansari Ansari; Abdul Aziz (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Family law is in an important position in the life of the community, contributing to creating and realizing an orderly and harmonious community environment. This research is based on the high rate of law violations in the family realm, such as divorce and domestic violence, which shows low awareness and compliance with family law. The method used in this study is libray research and the research approach uses a naturalistic method that is carried out at the time of natural setting, while the abjek that is studied is in accordance with the most appropriate conditions, then data collection techniques through participatory observation, and analysis of relevant legal and policy documents. The results of the study show that the implementation of family law supported by legal education, mediation, and community-based approaches can increase public understanding of the importance of family law, thereby encouraging law-abiding behavior. In addition, the results of the study also indicate that family law plays an important role as an effective social engineering tool in shaping legal norms and values that can increase legal awareness among the community.